PENGARUH LABA KOTOR, LABA OPERASI, DAN LABA BERSIH DALAM MEMPREDIKSI ARUS KAS MASA DEPAN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020–2024 - Ria Novita Sari; Indra Lila Kusuma; Hadi Samanto (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the influence of Gross Profit, Operating Profit, and Net Profit in predicting future cash flows in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This sector was chosen due to its crucial role in Indonesia’s economy and its consistent growth, despite challenges such as the COVID-19 pandemic, rising raw material costs, and intense market competition. In business operations, a healthy cash flow is vital to support daily activities, investments, and long-term sustainability. Therefore, the ability to predict future cash flows using financial indicators such as profits becomes essential. This research uses a quantitative approach with secondary data obtained from the financial reports published on the official IDX website. The results of the analysis show that Gross Profit, Operating Profit, and Net Profit all have a significant influence on future cash flows, both simultaneously and partially. These findings reinforce the role of profit metrics as effective predictive tools that management can use for strategic financial decision-making. This study is expected to contribute to the financial accounting literature and provide practical insights for investors, analysts, and company managers.